Bioconversion Impact of Pleurotus ostreatus on the Value of Rice and Groundnut By-products as Feed Resources - Issaka, Joseph Hamidu; Alemawor, Francis; Dzogbefia, Victoria Pearl (Research in Biotechnology, 2013)
<!–[if gte mso 9]> <![endif]–> The livestock industry in many developing countries is challenged with high cost of quality feed ingredients. For countries with agro-based economies, agro-industrial by-products are generated in large quantities but under-utilized and treated as Ã¢â‚¬Å“wastesÃ¢â‚¬Â. However their potential use as low-cost animal feed materials is challenged with digestibility problems and low protein content. In the present study sought to evaluate the potential of fungal biotechnological (bioconversion) pre-treatment of transforming two major agro-wastes, namely rice (Oryza glaberrima) straw and groundnut (Arachis hypogaea) shells, into valuable animal feeds. In a Completely Randomized Block Design, rice straw (RS), groundnut shells (GS) and a 1:1 ratio mixture of RS and GS were separately subjected to a 5-week Pleurotus ostreatus solid-state fermentation (SSF) process. The study demonstrated that P. ostreatus SSF increased (P<0.05) the level of limiting nutrients particularly, proteins and minerals (P, K and Ca) while at the same time decreasing the fibre and tannin levels to enhance their digestibility for monogastrics and ruminants. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>